Book Review: Entre la Espada y la Pared: Pedagogías de la Sexualidad en Torno a Moral Sexual. Prostitución de Hombres y Formación de Masculinidades en Costa Rica, by Luis Pablo Orozco Varela - Prada Ortiz, Grace (2021)
Presents a review of a book written by Luis Pablo Orozco Varela who, from an interdisciplinary approach, addresses the issue of male prostitution to discuss the processes of construction that take place on men’s sexuality. After a qualitative study, carried out in areas where prostitution is practiced, and based on interviews with various actors linked to the subject under study, the author develops a manuscript that leads the reader to observe the reality of a sector of the national population and thus place it as one of the pending issues to be addressed by Costa Rican society in the 21st century.